PENGEMBANGAN MODUL MIKROKONTROLLER CODEVISION AVR MENGGUNAKAN PERANGKAT LUNAK PROTEUS PROFESSIONAL PADA MATA PELAJARAN MIKROPROSESSOR DAN MIKROKONTROLLER UNTUK SISWA KELAS XI TEI SMKN 1 JETIS - Purnama, Rizki Dwi Putra; Harimurti, Rina; Widodo, Arif; Rahmadian, Reza (Universitas Negeri Surabaya, 2021)
Education is a place for the formation of a quality generation of the nation. Selection of learning media appropriately can increase the quality of learning in students. Microprocessors and microcontrollers are subjects that study software and hardware on computers The purpose of this study was to develop a codevision AVR microcontroller module using professional proteus software in microprocessor and microcontroller subjects for class students XI TEI SMKN 1 Jetis. In this research, the writer used research and development method and also gave pretest and posttest to 30 students. Retrieval of data with module validation sheets and questions that were validated by 2 lecturers majoring in Electrical Engineering and 1 teacher SMKN 1 Jetis which gets a rating of 84.3% for the module and 89.1% for the questions so that it produces a very valid media. Meanwhile, for the results of the analysis of the normality test using SPSS, the sig value is 0.200 for the pretest and 0.200 for the posttest which is normally distributed. In the T test using SPSS, it was obtained a significance value (2-tailed) of 0.000, so it was stated that there was a significant effect on the differences in the treatment given to each variable.